1976
DOI: 10.1007/bf00011130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur fertilization on the nitrogen-sulphur relationships in alfalfa (Medicago sativa L. Pers.)

Abstract: Distribution of different nitrogen and sulphur fractions and N:S ratios in alfalfa (Medicago sativa L. Pers.) without and with S fertilization has been studied with a green house experiment. With increasing rates of applied S, the concentrations of total N, protein N, total S, protein S and total soluble S in the plant increased but those of non-protein N fractions (total soluble N, amino acid N, amide N, nitrate N) decreased. Thus the adequate supply of S in alfalfa increases the protein synthesis by accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Our findings are consistent with data obtained for other legumes (DeBoer and Duke 1982;Zhao et al 1999;Scherer and Lange 1996). N and S are generally accumulated in proportion similar to those incorporated into proteins and S deficiency decreases protein synthesis, resulting in free amino acid accumulation (Dijkshoorn and Van Wijk 1967;Aulakh et al 1976;Karmoker et al 1991). Scherer and Lange (1996) postulated that these amino acids could have some feed-back repression on N 2 fixation.…”
Section: Fertilisation Effects On Sulphur and Nitrogen Acquisitionsupporting
confidence: 93%
“…Our findings are consistent with data obtained for other legumes (DeBoer and Duke 1982;Zhao et al 1999;Scherer and Lange 1996). N and S are generally accumulated in proportion similar to those incorporated into proteins and S deficiency decreases protein synthesis, resulting in free amino acid accumulation (Dijkshoorn and Van Wijk 1967;Aulakh et al 1976;Karmoker et al 1991). Scherer and Lange (1996) postulated that these amino acids could have some feed-back repression on N 2 fixation.…”
Section: Fertilisation Effects On Sulphur and Nitrogen Acquisitionsupporting
confidence: 93%
“…Scherer and Lange (1996) and Habtemichial et al (2007) found that S application increased nodule number and nodule fresh weight for a range of legume species (Medicago sativa, Trifolium pratense, Trifolium repens, Vicia faba and Pisum sativum), especially by enhancing root growth. Moreover, several authors suggested that S limitation triggers an increase in amino-acid content in plant tissue, which may subsequently down-regulate BNF (Dijkshoorn and Van Wijk 1967;Janssen and Vitosh 1974;Aulakh et al 1976;Scherer and Lange 1996). Therefore, a feed-back regulation by internal soluble reduced N (e.g.…”
Section: Sulphur Supplymentioning
confidence: 98%
“…Mineral nutrition, especially nitrogen (N) and S, are major factors affecting growth, yield, and quality of mustard (Aulakh, Dev, and Arora 1976;Aulakh, Parisha, and Sahota 1980;Ahmad et al 1998;Fodor and Kadlicskó 2006).…”
Section: Introductionmentioning
confidence: 99%